Branchial cleft cyst presenting as metastatic squamous carcinoma in fine needle aspirates: report of three case - Songu, Murat; Aslan, Hale; Başoğlu, Sinan; Öztürkcan, Sedat; Etit, Demet (ENT Updates, 2013)
A subset of metastatic squamous cell carcinoma of the head and neck presents as cystic masses in the neck. Often, distinguishing between these cystic metastases of squamous cell carcinoma from benign cystic neck lesions, such as branchial cleft cyst, can be very challenging. Squamous lining cells in benign cystic lesions may exhibit significant cytologic atypia, raising concern for squamous cell carcinoma. The challenge in distinguishing benign from malignant cystic squamous lesions of the neck is made more difficult when evaluating fine needle aspiration biopsies given the limited sample size. Herein, three patients with branchial cleft cysts are presented. All were initially diagnosed as metastatic squamous cell carcinomas. The importance of interpretation of fine needle aspiration cytology by an experienced cytologist is emphasized to avoid the possibility of excising metastatic squamous cell carcinomas, which could lead to unnecessary surgical procedures such as radical neck dissection.